Great Armenia and Euphrates Frontier in 60-s A.D. (Conflict, ideas, settlement) - Stepanyan, Albert; Minasyan, Lilit (ՀՀ ԳԱԱ հրատ.)
For centuries, the Euphrates River made up the border between Rome and the East – Iran, India, and China. The process of exchanging the values of culture and civilization took place across that border. It concerned economics and technologies, trade and military art, esthetics and religion. Հոդվածը խնդիր ունի լուսաբանելու հայոց պատմության մի հույժ կարևոր դրվագ՝ իր տարաբնույթ ընդգրկմամբ՝ ռազմական, դիվանագիտական, իրավական և այլն: Խոսքը, այսպես կոչված, պարթևահռոմեական տասնամյա պատերազմի (54–64) ընթացքի, ավարտի և արդյունքների նորմատիվ հաստատագրման մասին է: Целью статьи является освещение одного из важных фрагментов армянской истории в военном, дипломатическом и правовом аспектах. Речь идет о так называемой десятилетней войне (54–64 гг.) и нормативном урегулировании ее результатов с точки зрения международного права. Эта проблема уже более ста лет является предметом исследования многих ученых.
Keywords: History; Ancient History